Characterisation of an ultra low-background point contact HPGe well-detector for an underground laboratory. (April 2018) - Hult, Mikael; Marissens, Gerd; Stroh, Heiko; Lutter, Guillaume; Tzika, Faidra; Marković, Nikola
Abstract: Since a few years there are well-type HPGe-detectors with a small, point-like, anode contacts available commercially. This paper describes the characterisation of the first ultra low-background, so-called, SAGe™ well detector with regards to resolution and background performance. Inside a passive lead/copper shield in the underground laboratory HADES a background count rate of 690 ± 6 d −1 (268 ± 3 d −1 per kg Ge) was recorded 19 months after taking it underground. Highlights: The first ultra low background SAGe™ well detector was installed 225 m underground. It has an energy resolution superior to standard well Ge-detectors. The Ge mass is 2.57 kg corresponding to about 483 cm 3 . After 19 months underground, the background count rate 40–2700 keV was 690 d −1 . With muon-suppression the background count rate 40–2700 keV was 601 d −1 .